Research Progress on Cell-Free Biosensor and Its Application in Food and Biological Detection - WANG Jiajia, WANG Xin, PANG Xiaoxu, HUANG Kunlun, XU Wentao, LUO Yunbo, CHENG Nan (Shipin Kexue, 2023)
The cell-free biosensor is a tool designed to detect trace substances based on a cell-free system, which solves the problems of the traditional cell-based biosensor including having no ability to detect toxic substances, long response time, being controlled by living cells, and inconvenient operation. In recent years, cell-free biosensors have attracted extensive attention for their wide detection range, fast response speed, high sensitivity and portability. In this paper, the construction and characteristics of different types of cell-free sensors are reviewed. In addition, their applications in the detection of metal ions, pesticide residues and veterinary drug residues are introduced, and future prospects also are discussed.